An Experimental and Analytical Study on the Seismic Performance of Piers with Different Foundation Bottom Widths - Nagao, T.; Kurachi, Y. (Engineering, Technology & Applied Science Research, 2022)
Piers can be severely damaged by earthquakes. When an action of a massive earthquake is assumed, the seismic performance of the pier can be improved by widening the foundation width. A previous horizontal loading study indicated that extending only the Foundation Bottom (FB) width, rather than the complete foundation, can boost seismic resilience while suppressing the increase in building cost. However, the research dealt with only two types of FB width, i.e. normal and widened, and the data for sufficiently assessing the inclination angle of the pier with loading were not obtained. In this study, to evaluate the seismic performance of piers with different FB widths in more detail, horizontal loading tests on piers with ordinary columnar foundations and two types of piers with widened FB were conducted, and the seismic resistance of the three pier types were compared. It was shown that horizontal displacement and inclination angle of the pier can be reduced by widening the FB. Furthermore, finite element analysis was carried out to reproduce the experimental results. The analysis results showed good agreement with the experimental results in terms of pier horizontal displacement and inclination angle.